What makes health systems resilient? An analytical framework drawing on European learnings from the COVID-19 pandemic based on a multitiered approach - Thomas Czypionka; Markus Kraus; Miriam Reiss; Monika Riedel (BMJ Public Health)
Introduction The COVID-19 pandemic posed an unprecedented challenge, which caught many health systems widely unprepared. The aim of this research was to develop a comprehensive analytical framework on health system resilience in the context of pandemics. In addition to serving as a tool to analyse the preparedness and resilience of health systems, the framework is intended to provide guidance to decision-makers in health policy.Methods The analytical framework was developed based on a multitiered approach. A comprehensive review of the existing literature was conducted to identify relevant frameworks on health system resilience (published between 1 January 2000 and 30 November 2021) and determinants of resilience that emerged during the COVID-19 pandemic. Input was then gathered in several rounds of consultations with designated field experts and stakeholders, drawing on their experiences from the pandemic. Finally, the framework was empirically validated in several case studies.Results The framework distinguishes between prerequisites of resilience, pertaining to precautions to be taken in ‘normal’ times, and response strategies in the face of shocks. Both sections are further divided into six building blocks that were adapted from the WHO health system framework: governance and leadership, information and research, financing, physical resources, human resources, and service delivery. An overarching component on contextual factors—subdivided into situational, structural, cultural and international factors—represents an important addition to the existing spectrum of resilience frameworks.Conclusions Foundations for a resilient health system must be laid in ‘normal’ times and in all areas of the health system. In the face of a shock, adequate response strategies need to be developed. An essential learning from the COVID-19 pandemic has been that contextual factors of societies and subgroups play a major role in the ability of health systems to overcome a shock, as they impact the implementation and effectiveness of crisis management policies.